Trustee decisions in investment and finance - Weirich, Paul (Journal of business ethics, 1988)
When a trustee makes a decision for a client, a standard objective is to decide as the client would if he had the trustee's information. How can this objective be attained when, given the trustee's information, there is still uncertainty about the consequences of alternative courses of action? A promising approach is to apply the rule to maximize expected utility using the client's utilities for consequences and the trustee's probabilities for states. But taking utilities and probabilities from different sources causes a problem that has to be resolved. Briefly, the problem is that the client's utilities for consequences involve assessments of risks that are uninformed because he does not have informed probabilities. And the resolution of the problem is to reconstruct his utilities for consequences using a component due to risk that the trustee supplies for the client, and a component due to other consequences that the client supplies for himself.